Impact of transition in socio-economic status on sonographically detected non-alcoholic fatty liver disease: a study based on modified Kuppuswamy classification in an urban population - Jain, Abhinav; Manjavkar, Smita; Jafri, Humaid Ali; Anand, S. S. (International Journal of Research in Medical Sciences, 2020)
Background: The transition in the socioeconomic status is associated with physical and mental challenges. The lifestyle modification is one of the key implicatory for this change. Non-alcoholic fatty liver is an ever-growing health concern. This study evaluates the socioeconomic categories based on Kuppuswamy classification and other correlated in sonographically detected Non-alcoholic fatty liver disease (NAFLD). Methods: This cross-sectional study was conducted on 300 sonographically detected NAFLD patients in the age group of 18-60 years. Detailed history, including the demographic profile, socio-economic status (Modified Kuppuswamy scale was followed for calculating the Socio-economic status of the family), occupation, dietary habits (vegetarian or non-vegetarian, exposure to junk food), drinking water supply, etc. Detailed assessment of the morphological parameters including the anthropometric measurements, height, BMI was also assessed. Results: The study finds 62 (41%) females and 88 (59%) males with NAFLD and 51-60 age group with maximum prevalence. Diabetes (63%), Soft drink consumption and obesity are important risk factors. New observation of our study is that amongst various Kuppuswami sociodemographic scales, the maximum patients belonging to Upper middle class and upper lower class presented with fatty liver. Conclusions: There is higher prevalence of NAFLD amongst males, diabetics, obese, soft drinks, tea and coffee consumers. Authors also find a unique correlate based on socio-demographic class of Kuppuswami scale. People belonging to upper middle class and upper lower class suffer from NAFLD more commonly than other sociodemographic classes.